THE INFLUENCE OF TECHNOPRENEURSHIP AND BUSINESS NETWORK COMPETENCY TOWARDS THE COMPETITIVE ADVANTAGE OF SME IN THE MIDDLE OF THE COVID-19 PANDEMIC - Bangun Prajadi Cipto Utomo; Tri Djoko Santosa (ECONBANK: Journal of Economics and Banking, 2022)
The purpose of this study was to determine the partial and simultaneous positive effect of Technopreneurship Competence and Business Networks on the Competitive Advantage of MSMEs in the Midst of the Covid-19 Pandemic. The population of this research is SMEs in Surakarta. The research sample consisted of 100 MSMEs in Surakarta with used proportional random sampling. The data collection techniques used questionnaires and interviews. Multiple linear regression analysis was used to analyze the influence of Technopreneurship Competence and Business Networks in shaping the Competitive Advantage of MSMEs. The results show that technopreneurship competence and business networks have a significant effect on the competitive advantage of MSMEs in the culinary field in Surakarta. The contribution of independent variables consisting of technopreneurship competence and business networks to the competitive advantage of SMEs in the culinary field in Surakarta is 71.9% while the remaining 28.1% is influenced by other factors